Being as Principle: Unity and Systematicity in Rosmini’s Philosophy - Vargas, Jorge Alfonso (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
The article attempts to revalidate Antonio Rosmini’s philosophy by calling attention to the idea of being as the only idea necessary to build up all other ideas. In this way the author stresses the simplicity and unity of Rosmini’s system, comparing it with the systems of idealists who put too many innate ideas in their systems and with those of materialists who put none. The article analyses basically the fundamental experience, which allows one to distinguish between being, the only necessary idea, and sensation.
Keywords: sensation; existence; being; cognition